Parametric study on numerical simulation of the electromagnetic forming of DP780 steel workpiece with aluminium driver sheet. Issue 3 (August 2016) - Park, Hyeonil; Lee, Jinwoo; Kim, Se-Jong; Lee, Youngseon; Kim, Daeyong
Abstract: The purpose of this study is to investigate the influences of numerical parameters on the electromagnetic forming (EMF) simulation. The 3-dimensional coupled electromagnetic- mechanical simulations were conducted to predict the deformation behavior of the advanced high strength steel (AHSS) sheet receiving support in EMF with aluminum driver sheet. Dual phase (DP) 780 steel workpiece was formed into a hemi elliptical protrusion shape with aluminum alloy AA1050 driver sheet using a flat spiral coil actuator and open cavity die. The deformed shape of the DP780 workpiece and the computation time with respect to element size, N cycle number and time step of electromagnetic (EM) solver were analysed.